Kontribusi Pertunjukan Seni Tari Tradisional Sebagai Atraksi Wisata Terhadap Kesejahteraan Masyarakat Lokal Desa Adat Ubud - Ni Gusti Ayu Eka Putri; Putri Kusuma Sanjiwani (JURNAL DESTINASI PARIWISATA, 2021)
Ubud which is famous for cultural tourism has encouraged the local community to participate in these tourism activities. Performing traditional dance that develops in every banjar in Ubud by involving local communities in the implementation will certainly contribute to the lives of people in Ubud both material and non-material. This study aims to determine the contribution of traditional dance performances as a tourist attraction to the welfare of local communities in the Indigenous Village of Ubud, Ubud District, Gianyar Regency.In this study using primary data sources and supported by secondary data obtained directly by observation and interviews, and the data analysis technique used in this study is qualitative analysis by reducing data which is then presented and concluded. The results of this study show that the contribution of traditional performing arts to the welfare of the local community can be seen from the community's involvement, either directly or indirectly. Being involved in performance performances is a side profession for the local community. Apart from helping economically, the results of this art performance can also contribute to the socio-cultural field of the community in traditional villages.Keyword: Contributions, Performing Arts, Prosperity, Local Communities